Pengaruh Word Of Mouth Terhadap Keputusaan Mahasiswa Himpunan Mahasiswa Kecamatan Bantan Memilih Bank Syariah - Azlina, Nur; Noratika, Noratika (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
This study aims to determine the effect of word of mouth on the decision of Kecamatan Bantan students to choose Islamic banks. The research method uses a quantitative descriptive approach. The population is all students in the Kecamatan Bantan student association with a total of 157 people. The number of samples is 61 people with the sampling technique used is the random sampling method. The data analysis technique used simple linear regression. The marketing level of word of mouth (X) in the Bantan sub-district student association is included in the high category, namely 76.58%. The decision level (Y) is included in the high category, namely 80.20%. The results showed that the word of mouth variable had an effect on students' decisions to choose Islamic banks. The results of the study can be considered by Islamic banks in making policies.